A Live Baby Resulting Out of a Term abdominal Pregnancy: A Case Report - Raut, Bhaktabatsal; Acharya, Shreedhar (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5064 NJOG 2010 Jul-Aug; 5(1): 55-57